An initial exploration on framework of data assetization - Yazhen YE; Guohua LIU; Yangyong ZHU (大数据)
As the digital economy develops,data as one of the key elements of the digital economy has been widely recognized as a new type of assets.However,various types of data cannot be treated as assets.Therefore,the criteria of data assets and the transformation from datasets to data assets are critical questions for data industry and the actors involved in data economy to solve.The features and requirements of data assets were discussed,and a basic framework for data assetization based on features of data assets was proposed,including five phases of registration of rights concerning data resources,data value confirmation and quality control,data box building and storage,asset pricing and evaluation,and data asset depreciation and appreciation management.A plausible path to data resource assetization was provided.